Effects of Video Game Playing on Social Intelligence, Aggression, and Loneliness among University Students - Preetika Mohta; Atreyee Bhattacharyya (International Journal of Indian Psychȯlogy, 2022)
This study aimed to investigate the association between gender, game playing status, and psychosocial factors, including social intelligence, aggression, and loneliness, among college and university students. The study involved 200 college and university students aged 18-25, comprising 102 females and 98 males. Participants were categorized as game players (65%) and non-players (35%) based on their gaming status. Participants completed three questionnaires assessing social intelligence, aggression, and loneliness. Statistical analyses included chi-square tests, Kruskal-Wallis tests, correlation analysis, and linear regression to explore relationships between variables. Significant findings included a gender disparity in game playing status (p < 0.001), with more males playing video games. Social intelligence was significantly associated with gender (p = 0.043) and age (p = 0.033). No significant gender differences were observed in aggression or loneliness. Correlation analysis revealed weak relationships between variables. Social information processing significantly predicted aggression (p = 0.020). This study highlights gender differences in video game engagement, with males more inclined to play. Social intelligence was influenced by gender and age, but aggression and loneliness showed no significant gender differences. The study emphasizes the need for further research on the complex relationships between video game playing, psychosocial factors, and gender. These findings underscore the importance of considering gender and age in interventions related to social intelligence. Future research should explore the nuanced effects of video game content on psychosocial outcomes among college and university students and consider broader factors influencing loneliness.